Intestinal metabolites and the risk of autistic spectrum disorder: A two-sample Mendelian randomization study - Liu, Deyang; Bu, Dengyin; Li, Hong; Wang, Qingsong; Ding, Xudong; Fang, Xiaolu (Frontiers in Psychiatry, 2023)
Background: Observational studies have reported a strong association between Autistic Spectrum Disorder (ASD) and intestinal metabolites. However, it is unclear whether this correlation is causally or violated by confounding or backward causality. Therefore, this study explored the potential causal relationship from intestinal metabolites dependent metabolites on ASD. Method: We used two sample Mendelian random analysis and selected genetic loci closely related to intestinal flora dependent metabolites as instrumental variables. MR-Egger, inverse variance weighted (IVW), MR-PRESSO, maximum likelihood, and weighted median were performed to reveal their causal relationships. Ten metabolites were studied, which included trimethylamine-N-oxide, betaine, carnitine, choline, glutamate, kynurenine, phenylalanine, serotonin, tryptophan, and tyrosine. Sensitivity were also performed to evaluate the robustness of the MR study. Results: Results of the IVW method revealed that serotonin increases the ASD risk (OR 1.060, 95% CI: 1.006-1.118) while choline could decrease the ASD risk (OR 0.925, 95% CI: 0.868-0.988). However, no definite causality was observed between other intestinal metabolites (e.g., trimethylamine-N-oxide, betaine, carnitine) with ASD. Additionally, neither the funnel plot nor MR-Egger test showed horizontal pleiotropy, and MR-PRESSO found no outliers. Cochran’s Q test showed no significant heterogeneity among the studies, suggesting the robustness of the study. Conclusions: Our study found potential causality from intestinal metabolites on ASD. Clinicians are encouraged to offer preventive measures to such populations. Keywords: Autistic Spectrum Disorder; Intestinal metabolites; Mendelian randomization; Causality